Low-cost formation of bulk and localized polymer-derived carbon nanodomains from polydimethylsiloxane - Alcántara, Juan Carlos Castro; Cerda Zorrilla, Mariana; Cabriales, Lucia; Rossano, Luis Manuel León; Hautefeuille, Mathieu (Beilstein Journal of Nanotechnology, 2015)
We present two simple alternative methods to form polymer-derived carbon nanodomains in a controlled fashion and at low cost, using custom-made chemical vapour deposition and selective laser ablation with a commercial CD-DVD platform. Both processes presented shiny and dark residual materials after the polymer combustion and according to micro-Raman spectroscopy of the domains, graphitic nanocrystals and carbon nanotubes have successfully been produced by the combustion of polydimethylsiloxane layers. The fabrication processes and characterization of the byproduct materials are reported. We demonstrate that CVD led to bulk production of graphitic nanocrystals and single-walled carbon nanotubes while direct laser ablation may be employed for the formation of localized fluorescent nanodots. In the latter case, graphitic nanodomains and multi-wall carbon nanotubes are left inside microchannels and preliminary results seem to indicate that laser ablation could offer a tuning control of the nature and optical properties of the nanodomains that are left inside micropatterns with on-demand geometries. These low-cost methods look particularly promising for the formation of carbon nanoresidues with controlled properties and in applications where high integration is desired.
Keywords: carbon nanodomains; nanodots; polydimethylsiloxane; polymer-derived ceramics; Raman spectroscopy